Two-dimensional multiphase non-isothermal modeling of a flowing electrolyte – Direct methanol fuel cell. (26th January 2017) - Atacan, O.F.; Ouellette, D.; Colpan, C.O.
Abstract: A two-dimensional, non-isothermal, two-phase model is developed to investigate the non-isothermal and thermo-osmotic behavior within a flowing electrolyte direct methanol fuel cell (FE-DMFC). The physics of this fuel cell are examined and discussed for varied anode and cathode inlet temperatures, with particular emphasis being placed on the non-isothermal behavior of this fuel cell. The results show that the cathode's thermal entrance length is much larger than that of the anode's, and that the cathode's inlet temperature influences the overall cell temperature more significantly than that of the anode's. This was found to be primarily due to the cathode's high velocity and molecular diffusivity, which allowed for a high degree of convective cooling. This effect was found to cause the mid-plane temperature to be ∼10 °C lower than that of the set point temperature for the coldest air inlet temperature of 40 °C. Furthermore, it was also found that possible flooding conditions could occur within the cathode air channel, if either the anode's or cathode's inlet temperature is too low, relative to the fuel cell's set point temperature. Highlights: Derivation of single domain non-isothermal MMM for FE-DMFC. Full coupling and description of thermo-osmotic fluxes for all species. Cathode's inlet temperature most significantly effects cell temperature. Flooding in CAC could occur if anode or cathode inlet temperatures too low.